Effects of trehalose on bone healing, physical function, and pain in patients with pertrochanteric fractures: a randomized controlled trial protocol - Reza Zandi; Hosna Omidi Razani; Amir Mehrvar; Mohammad-Reza Jowshan; Amirhossein Sahebkar; Bahar Nikooyeh; Hoda Zahedi; Shahin Talebi (Trials)
Abstract Background Appropriate management of fractures is crucial for restoring natural bone function and preventing long-term complications. Previous research on animal models indicates that trehalose can improve bone fracture healing by inhibiting the inflammatory cascade. We hope that trehalose can accelerate bone fracture healing in humans, alleviate pain, and ultimately enhance the individual’s quality of life. Methods This randomized, double-blind clinical trial will be conducted at Taleghani Hospital in Tehran, Iran. Sixty-four patients admitted to the orthopedic ward will be enrolled based on eligibility criteria. The participants will be randomly allocated based on the permuted block randomization into two groups: those receiving trehalose (32 patients) or placebo (32 patients). The patients in the trehalose and placebo groups will receive 3.3 g of trehalose or placebo for 12 weeks, respectively. A consent form, general questionnaire, as well as the Visual Analog Scale (VAS), Harris Hip Score (HHS), and radiological analyses will be used to assess fracture healing quality. The intention-to-treat principle will form the basis of the statistical analysis. Discussion The trial results may provide a convenient and safe adjuvant treatment option for the Pertrochanteric Fractures population. Trial registration Iranian Registry of Clinical Trials. IRCT20240605062013N1. URL of the trial registry record: https://irct.behdasht.gov.ir/trial/77212 . Registration date: 16 June 2024.